SECURITY ASPECTS OF DIGITAL TRANSACTIONS E-COMMERCE AND M-COMMERCE IMPLEMENTATIONS - Kiselichki, Martin; Kirovska, Zanina; Anastasovski, Milan; Jovevski, Dimitar (Institute for Knowledge Management, 2022)
Through the accelerated digitization in business, new models of digital transactions are becoming more popular in the last few years. In electronic commerce, in addition to the standard models of B2B (business to business) and B2C (business to customers), m-commerce is becoming increasingly popular, which is defined as conducting e-commerce through wireless communication devices, smartphones and tablets. M-commerce is a new and cutting-edge way of doing business in the world. M-commerce is carried out through mobile devices and appropriate data transfer protocols. This way of doing business is on the rise in the world because the user is not bound to place and time, the service is available anywhere at any time. The paper defines the differences between typical models of e-commerce and m-commerce, in order to make a clear distinction between them. The growth of m-commerce has been investigated in more detail through available statistics and other secondary sources, where trends can also be determined in the next few years, where it is assumed to become one of the dominant patterns of online transactions. The increase in transactions through digital channels also leads to new dangers and security threats, which are amplified because they are new and less tested technologies that could have security flaws. The paper explores the various security threats in e-commerce and m-commerce through analysis and synthesis, where it is shown that there are six different aspects, including integrity, non-repudiation, authenticity, confidentiality, privacy and availability. These aspects are analyzed in more detail through their special elements, as well as the possible strategies for their management. Security, as a very important issue in e-commerce systems, should be taken under the control of companies and government institutions. To this end, a well-managed technology-based strategy should be implemented. A special focus is devoted to the risks and threats in e-commerce, as well as defining the different types of cybercrime that characterize these digital transactions. Through the presentation of the various security aspects of e-commerce and m-commerce, the paper contributes to a better understanding and formation of strategies to deal with the security of transactions with the help of these digital technologies, as well as more frequent changes and synchronization of legal regulations by the institutions in charge of the same ones. Trust in these types of transactions is one of the key elements for their projected growth in the future, making the perception of security vital in the online shopping decision.
Keywords: E-commerce, m-commerce, computer crime, security, m-commerce threats